2022
DOI: 10.4081/jphr.2021.2099
|View full text |Cite
|
Sign up to set email alerts
|

The Association among Health Behaviors, Shift Work and Chronic Morbidity: A Cross-Sectional Study on Nurses Working in Full-Time Positions

Abstract: Background: Nurses are known to work in conditions of stress and physical overload. Health behaviors are modifiable factors that may reduce the adverse effects of work on general health. The present study examined health-related behaviors and their association with current night shift work and chronic morbidity among female nurses.Design and Method: Four hundred seventy-two female nurses (M ± SD = 44.28±7.14 years) self-reported their health habits, physical activity, body mass index (BMI), and chronic disorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…For example, increased risk for cardio-vascular, gastro-intestinal, and metabolic diseases ( James S.M. et al, 2017 ; Berent et al, 2022 ), in particular for night or rotating shift workers ( Caruso et al, 2006 ). Police officers are more likely to suffer from these diseases than other workers ( Tuttle et al, 2019 ), in addition to disproportionately suffering from sleep disorders ( Vila, 2000 ; Vila, 2006 ; Rajaratnam et al, 2011 ; James et al, 2022 ), impaired domestic relationships and reduced quality of life ( James et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, increased risk for cardio-vascular, gastro-intestinal, and metabolic diseases ( James S.M. et al, 2017 ; Berent et al, 2022 ), in particular for night or rotating shift workers ( Caruso et al, 2006 ). Police officers are more likely to suffer from these diseases than other workers ( Tuttle et al, 2019 ), in addition to disproportionately suffering from sleep disorders ( Vila, 2000 ; Vila, 2006 ; Rajaratnam et al, 2011 ; James et al, 2022 ), impaired domestic relationships and reduced quality of life ( James et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Support of both short and long-term health of nurses is imperative to ensure an adequate workforce is available to provide vital healthcare services to community members across the spectrum of wellbeing and illness. Studies have demonstrated an inherent connection between self-care activities of physical activity (PA), diet quality, sleep hygiene, and physical/mental health in the nursing workforce ( Berent et al, 2021 ; Jiang et al, 2021 ; Mazurek Melnyk et al, 2022 ). For example, high-quality sleep, healthy eating habits, and regular physical activity are associated with a reduced risk of psychological conditions such as stress and burnout ( Fitzpatrick & Valentine, 2021 ) and lower risk for all-cause mortality ( Saeidifard et al, 2019 ; Sotos-Prieto et al, 2017 ; Yin et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have explored the attitudes of healthcare professionals toward health behaviors, revealing mixed findings [25][26][27][28][29]. Despite their awareness of the importance of regular physical activity, medical professionals exhibit similar engagement levels as the general population.…”
Section: Introductionmentioning
confidence: 99%